Chromatin modifiers in neurodevelopment - Rezazadeh, Sarallah; Ji, Hong; Giulivi, Cecilia (Frontiers in Molecular Neuroscience, 2025)
Emerging sequencing studies highlight the critical role of chromatin regulatory mechanisms in human diseases, particularly in neurodevelopmental and neurological disorders. Insights gained from these studies and model organism research reveal the intricate involvement of chromatin regulators in neurodevelopment, raising compelling questions about how mutations in these ubiquitous proteins drive specific dysfunctions in the nervous system. This mini review delves into key chromatin modifiers, including the histone methyl transferases NSD1 and ASH1L, the methyl-CpG-binding repressor MeCP2, and the enzymatic repressor EZH2. While functions of these proteins are relatively well-studied, the roles of many other chromatin modifiers in neurodevelopment remain poorly understood. Existing therapies targeting chromatin modifiers have shown promise, with some achieving significant clinical success. The possibility that neurological dysfunctions may be treatable even later in life underscores the urgency of prioritizing chromatin modifiers as therapeutic targets. In this mini review, we critically evaluate the current understanding of chromatin modifiers, focusing on methylation, and spotlight their pivotal roles in early brain development and neurological disorders. By advancing this field, we aim to inspire progress toward innovative treatments for these challenging conditions.